(untitled) (UNIZIK Journal of STM Education, 2021)
This study investigated the production-based and demonstration instructional approach on pre-service Chemistry teacher’s academic achievement. One research question and one hypothesis guided the study. The study adopted a non-equivalent control group quasi experimental design. The study was conducted in four Colleges of Education in the South East Geo-political zone. Out of the four schools, two colleges were exposed to the use of production-based and demonstration instructional approach (experimental group), while the other two were exposed to conventional lecture method (control group). 150 pre-service Chemistry students participated in the study. Production-based chemistry achievement test (PCAT) which was developed by the researchers was used as an instrument for data collection. PCAT was subjected to face and content validation. Its reliability was established at 0.87 using Kuder-Richardson formula 21(K-R-21). Mean and standard deviation as well as analysis of covariance (ANCOVA) were used to answer the research question and test the hypothesis at 0.05 level of significance respectively. The result of the study revealed that the production based and demonstration was significance at 0.05 probability level in enhancing the academic achievement in pre-service Chemistry teachers. It also revealed that gender had no effect on the level of academic achievement of pre-service Chemistry teachers. Based on these findings, recommendations were made which included that Chemistry teachers should adopt demonstration with production-based instructional approach in enhancing academic achievement in pre-service Chemistry teachers.